Existence of Mild Solutions of Abstract Fractional Differential Equations with Fractional Non-Instantaneous Impulsive Conditions - Anguraj, A.; Kanjanadevi, S.; Trujillo, Juan J. (Discontinuity, Nonlinearity, and Complexity, 2026)
We study the existence and uniqueness of a mild solution of fractional impulsive differential equations with nonlocal conditions. Here we consider fractional derivative in the non-instantaneous impulsive conditions. We use fixed point techniques and resolvent operators to prove our existence results.